Physics of Pair-producing Gaps in Black Hole Magnetospheres: Two-dimensional General Relativistic Particle-in-cell Simulations - Yajie Yuan; Alexander Y. Chen; Martin Luepker (The Astrophysical Journal)
Black holes can launch powerful jets through the Blandford–Znajek process. This relies on enough plasma in the jet funnel to conduct the necessary current. However, in some low-luminosity active galactic nuclei, the plasma supply near the jet base may be an issue. It has been proposed that spark gaps—local regions with unscreened electric field—can form in the magnetosphere, accelerating particles to initiate pair cascades, thus filling the jet funnel with plasma. In this paper, we carry out 2D general relativistic particle-in-cell (GRPIC) simulations of the gap, including self-consistent treatment of inverse Compton scattering and pair production. We observe gap dynamics that is fully consistent with our earlier 1D GRPIC simulations. We find strong dependence of the gap power on the soft photon spectrum and energy density, as well as the strength of the horizon magnetic field. We derive physically motivated scaling relations, and applying to M87, we find that the gap may be energetically viable for the observed TeV flares. For Sgr A*, the energy dissipated in the gap may also be sufficient to power the X-ray flares.